A Black Phosphorus–Graphite Composite Anode for Li‐/Na‐/K‐Ion Batteries. Issue 6 (20th December 2019) - Jin, Hongchang; Wang, Haiyun; Qi, Zhikai; Bin, De‐Shan; Zhang, Taiming; Wan, Yangyang; Chen, Jiaye; Chuang, Chenghao; Lu, Ying‐Rui; Chan, Ting‐Shan; Ju, Huanxin; Cao, An‐Min; et al.
Abstract: Black phosphorus (BP) is a desirable anode material for alkali metal ion storage owing to its high electronic/ionic conductivity and theoretical capacity. In‐depth understanding of the redox reactions between BP and the alkali metal ions is key to reveal the potential and limitations of BP, and thus to guide the design of BP‐based composites for high‐performance alkali metal ion batteries. Comparative studies of the electrochemical reactions of Li +, Na +, and K + with BP were performed. Ex situ X‐ray absorption near‐edge spectroscopy combined with theoretical calculation reveal the lowest utilization of BP for K + storage than for Na + and Li +, which is ascribed to the highest formation energy and the lowest ion diffusion coefficient of the final potassiation product K3 P, compared with Li3 P and Na3 P. As a result, restricting the formation of K3 P by limiting the discharge voltage achieves a gravimetric capacity of 1300 mAh g −1 which retains at 600 mAh g −1 after 50 cycles at 0.25 A g −1 . Abstract : Into the black : The energy‐storage properties of black phosphorus are reported for Li/Na/K ion batteries. BP shows the lowest utilization for K + storage than for Na + and Li +, which is ascribed to the highest formation energy and the lowest ion diffusion coefficient of the final potassiation product K3 P compared with Li3 P and Na3 P.